INOVASI PAVING BLOCK BERBAHAN DASAR LIMBAH PLASTIK SEBAGAI MATERIAL KONSTRUKSI RAMAH LINGKUNGAN DI DESA PADANG MAINU - Daniel Refandi Sibarani; Dwika Novalia; Endah Ayu Fadhila; Enos Saputra Sidabutar; Fransisco Mezgion Hutauruk; Yusmalinda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The increasing amount of plastic waste in the community has become an environmental problem that requires innovative and sustainable solutions. This community service activity was carried out as an effort to empower the residents of Padang Mainu Village through education and practical training in processing plastic waste into environmentally friendly paving blocks using used oil as a melting medium and sand as a reinforcing material.The implementation included socialization on the environmental impacts of plastic waste, training on the plastic processing and melting process, mixing with sand, molding, and simple testing of the final product. The results showed that the community was able to independently produce paving blocks with adequate physical quality for non-structural use.This community service program successfully increased community awareness in managing plastic waste, reduced waste volume, and created opportunities for recycling-based economic activities. Overall, this program represents a simple, practical, and sustainable solution to support community-based waste management.